Traffic Conditions and Characteristics: Investigation of Road Segment Performance - St. Maryam Hafram; Ahmad Rifqi Asrib (Three E Science Institute, 2022)
The dimensions of the road affect the flow of traffic passing over it. Even though the traffic lanes are the same width, the traffic flow will not be the same because the environment is different. This study aims to determine traffic conditions and characteristics through density analysis and the level of traffic service on the roads. This research is a type of non-experimental research, like a case study with survey methods and direct field observations to determine the performance of the road network. The primary data collected through direct recording in the field is the number of vehicles passing through Perintis Kemerdekaan Road and observing the side constraints that reduce capacity and service levels and impede smooth traffic flow. Data analysis used the Highway Capacity Manual (HCM) and Indonesia Road Capacity Manual (MKJI) 1997. The service level value (LOS) is obtained by dividing the peak traffic volume in the west direction of 4728 PCU/hour with the road capacity value obtained by the service level of 0.89 entering category E while in the east direction with a traffic volume value of 4974 PCU/hour obtained the degree of saturation value of 0.94. The results of the study show that the level of road service is between (D - E) with a value of 0.85 to 1.00, which means that it is close to road capacity and sluggish speed, high traffic density due to internal barriers and vehicle drivers who experience traffic jams of medium duration.